The bone Gla protein osteocalcin is expressed in cranial neural crest cells - Rotem Kalev-Altman; Veatriki Fraggi-Rankis; Efrat Monsonego-Ornan; Dalit Sela-Donenfeld (BMC Research Notes)
Abstract Background Osteocalcin is a small protein abundant in the bone extracellular-matrix, that serves as a marker for mature osteoblasts. To become activated, osteocalcin undergoes a specific post-translational carboxylation. Osteocalcin is expressed at advanced stages of embryogenesis and after birth, when bone formation takes place. Neural crest cells (NCCs) are a unique cell population that evolves during early stages of development. While initially NCCs populate the dorsal neural-tube, later they undergo epithelial-to-mesenchymal-transition and migrate throughout the embryo in highly-regulated manner. NCCs give rise to multiple cell types including neurons and glia of the peripheral nervous system, chromaffin cells and skin melanocytes. Remarkably, in the head region, NCCs give rise to cartilage and bone. Finding: Here we report that osteocalcin is detected in cranial NCCs. Analysis of chick embryos at stages of cranial NCC migration revealed that osteocalcin mRNA and protein is expressed in pre-migratory and migratory NCCs in-vivo and ex-vivo. Addition of warfarin, an inhibitor of osteocalcin carboxylation, onto neural-tube explants, reduced the amount of NCC migration. These results provide the first evidence of osteocalcin presence in cranial NCCs, much before they give rise to craniofacial skeleton, and propose its possible involvement in the regulation of NCC migration.